Total weight loss induces the alteration in thyroid function after bariatric surgery - Tian, Ziru; Nie, Yuntao; Li, Zhengqi; Wang, Pengpeng; Zhang, Nianrong; Hei, Xiaofan; Ping, An; Liu, Baoyin; Meng, Hua (Frontiers in Endocrinology, 2024)
Background: Bariatric surgery is an effective approach to weight loss, which may also affect thyroid function. However, alteration in thyroid-stimulating hormone (∆TSH) and thyroid hormones after bariatric surgery and the relationship between thyroid function and postoperative weight loss still remains controversial. Methods: Data were collected from euthyroid patients with obesity who underwent sleeve gastrectomy and Roux-en-Y gastric bypass from 2017 to 2022. The alterations of free thyroxine (FT4), free triiodothyronine (FT3), total thyroxine (TT4), total triiodothyronine (TT3), and TSH were calculated 1 year after surgery. Pearson correlation analysis was used to assess the correlation between the percentage of total weight loss (%TWL) and ∆TSH. Multivariable linear regression was utilized to determine the association between %TWL and ∆TSH. Results: A total of 256 patients were included in our study. The mean %TWL was 28.29% after 1 year. TSH decreased from 2.33 (1.67, 3.04) uIU/mL to 1.82 (1.21, 2.50) uIU/mL (P<0.001), FT3 decreased from 3.23 ± 0.42 pg/mL to 2.89 ± 0.41 pg/mL (P<0.001), FT4 decreased from 1.11 ± 0.25 ng/dL to 1.02 ± 0.25 ng/dL (P<0.001), TT3 decreased from 1.13 (1.00, 1.25) ng/mL to 0.89 (0.78, 1.00) ng/mL (P<0.001), and TT4 decreased from 8.28 ± 1.69 ug/mL to 7.82 ± 1.68 ug/mL 1 year postoperatively (P<0.001). %TWL was found to be significantly correlated to ∆TSH by Pearson correlation analysis (Pearson correlation coefficient = 0.184, P = 0.003), indicating that the more weight loss, the more TSH declined. After adjusting for covariates in multivariable linear regression, %TWL was found to be independently associated with ∆TSH (β = 0.180 [95% confidence interval (CI), 0.048–0.312], P = 0.008). Moreover, %TWL was divided into 3 categorical groups (%TWL ≤ 25%, 25% < %TWL ≤ 35%, and %TWL > 35%) for further exploration, and was also found to be an independent predictor for ∆TSH after adjusting for covariates in multivariable linear regression (β = 0.153 [95% CI, 0.019–0.287], P = 0.025). Conclusion: TSH, FT4, FT3, TT4, and TT3 decrease significantly 1 year after bariatric surgery. The decline in TSH is independently mediated by postoperative weight loss; the more the weight loss, the more the TSH decrease.